A Network of Resistances against a Multiple Crisis. SOS Rosarno and the Experimentation of Socio-Economic Alternative Models - Oliveri, Federico (PARTECIPAZIONE E CONFLITTO, 2015)
SOS Rosarno was launched in 2011 by a group of small farmers and activists based in the Gioia Tauro Plain, Calabria, Southern Italy. The idea was to sell organic citrus fruits through short self-organized supply chains, essentially based on Solidarity Purchase Groups, in order to allow producers to pay migrant workers according to the law, to receive a fair remuneration, to guarantee healthy and affordable food to consumers, to protect the integrity of the environment. This paper aims to reconstruct the ideological frame and the genealogy, the organization and the practices, the impact and the limits of SOS Rosarno, drawing mainly on the political documents produced by the association and in-depth interviews with its diverse members. It clarifies, on one side, the strategies of alternative economy and the new social alliances implemented in order to challenge those conditions which impoverish small producers and let migrant farmworkers be exploited and become the target of racism in many Italian countrysides. It explores, on the other side, the development of a new peasant civilization as alternative to the current economic and environmental crises, in terms of de-commodification of nature and labour, construction of a convivial democratic society, transition from monoculture to food sovereignty.